Performance musical na cultura popular contemporânea de João Pessoa/PB - Ribeiro, Fábio Henrique Gomes (2017)
Until the 1960s-1980s, in the metropolitan region of João Pessoa, Paraíba, Brazil, musical expressions of popular culture had essentially communitarian performances, with participatory features and financed by donations. After this period, the presentational structures have grown as performance model, incorporating a set of experiences and meanings emerged from a socio-collaborative network composed of participants from different groups, folklorists, academics and political agents. Considering this context, this work presents, analyses and reflects on the fundamental contemporary dimensions that characterize and cross the musical performance of two popular culture groups in the metropolitan region: Barca Nau Catarineta de Cabedelo/PB and Ciranda do Sol, Novais District, João Pessoa/PB. The methodological basis consisted of ethnographic research developed between 2013 and 2016, with participant observation, interviews and audio-visual records. From a bibliographical research developed in this same period, the epistemological and theoretical dimension is based mainly on the musical performance studies and popular culture, articulating areas like ethnomusicology, anthropology and sociology. The processes of social interaction and the production of collective experiences in performance guide the musical performance approach. The results point to a multifaceted socio-interactive reality mediated by the sensitive experiences of the performance, producing musical experiences assessed subjectively and collectively in the contexts studied. The interpretations lead to ground the thesis that sociointeractive process involving the evocation, production and sharing of experiences and individual and collective meanings defines the contemporary musical performance of groups. I argue that the contemporary dimensions of the Barca?s and Ciranda?s musical practices are constructed by the social and symbolic interaction between the subjects and their collectivity, mediated by experiences and meanings emanating on political, cultural, social, aesthetic and economic dimensions. The aesthetic dimensions are understood as all forms of perception and apprehension of the socio-cultural environment. Thus, these dimensions presented themselves as the main mediators of the process, evoking past experiences and constructing new experiences and meanings from the interaction with the others.